Wunschmaschine Welterfindung : Eine Geschichte der Technikvisionen seit dem 18. Jahrhundert - Berr, Marie-Anne; Chemineau, Manuel; Druckrey, Timothy; Fassler, Manfred; Federmair, Leopold; Felderer, Brigitte; Fuchs, Mathias; Gray, Charles Hables; Hadid, Zaha; Hajos, Géza; Huhtamo, Erkki; Kittler, Friedrich; et al. (Wien - New York : Springer Verlag, 1996)
ARCHIMEDIA, Christian Möller / ; ART + COM ; Acconci, Vito ; Adolfo Natalini & Superstudio ; Anderson, Theodore E. ; Arbib, Richard ; Artzybatsheff, Boris ; Bacon, Francis ; Belarski, Emile & A. de Rudolph ; Bok, Hannes ; Bonestell, Chesley ; Broodthaers, Marcel ; Buckminster Fuller, Richard ; Böhrs, Hermann ; Carrouges, Michel ; Cartier-Bresson, Henri ; Coggins, Jack ; Cook, Peter ; Coop Himmelb(l)au ; Crompton, Dennis ; Delafosse, Jean-Charles ; Döring, Wolfgang ; Fagg, Kenneth ; Ferry, Jean ; Finlay, Virgil ; Forest, Jean Claude ; Freeman, Fred ; Friedman, Yona ; Fuchs, Mathias ; Future Systems ; Gehrmann, Hasso ; Gernreich, Rudi ; Gilbreth, Frank B. & Lilian ; Greene, David ; Groebli, René ; Halley, Peter ; Hampson, Frank ; Haus-Rucker-Co ; Heath, Russ ; Herdeg, Hugo Paul ; Hergé ; Herron, Ron ; Hollein, Hans ; Jonas, Walter ; Lachmann, Alex ; Lassnig, Maria ; Le Corbusier ; Leger, Fernand ; Leydenfrost, Alexander ; Lissitzky, El ; Magritte, René ; Malevich, Kasimir ; Marshall, William ; Matta-Clark, Gordon ; Maymont, Paul ; Mayrowitz, David Lane ; Mézières, Jean-Claude ; Pal, George ; Panamarenko ; Pannaggi, Ivo ; Paolozzi, Eduardo ; Paul, Frank R. ; Picabia, Francis ; Pichler, Walter ; Pioch, Ray ; Pircher, Wolfgang ; Rauschenberg, Robert ; Rossi, Christine G. ; Roussel, Raymond ; Sermon, Paul ; Shatalov, Vladmir Aleksandrovich ; Shortshanks ; Signer, Roman ; Smith, Malcolm ; Smithson, Robert ; Stelarc ; Suquet, Jean ; Valigursky, Edward ; Walduck, Desmond ; Watson, Keith ; Webb, Michael ; Webber, Francisco de Sousa ; Weibel, Peter
Wunschmaschine Welterfindung : Eine Geschichte der Technikvisionen seit dem 18. Jahrhundert, Kunsthalle Wien, 5. Juni - 4. August 1996
Duits
kunstcatalogus